Advances on Microsized On‐Chip Lithium‐Ion Batteries. Issue 45 (27th September 2017) - Liu, Lixiang; Weng, Qunhong; Lu, Xueyi; Sun, Xiaolei; Zhang, Lin; Schmidt, Oliver G.
Abstract: Development of microsized on‐chip batteries plays an important role in the design of modern micro‐electromechanical systems, miniaturized biomedical sensors, and many other small‐scale electronic devices. This emerging field intimately correlates with the topics of rechargeable batteries, nanomaterials, on‐chip microfabrication, etc. In recent years, a number of novel designs are proposed to increase the energy and power densities per footprint area, as well as other electrochemical performances of microsized lithium‐ion batteries. These advances may guide the pathway for the future development of microbatteries. Abstract : Microsized lithium–ion batteries should become a promising power supply for various next‐generation miniaturized electronic devices, once the challenges associated with the structural design and fabrication are solved.